2020
DOI: 10.1002/dad2.12051
|View full text |Cite
|
Sign up to set email alerts
|

Subjective cognitive and non‐cognitive complaints and brain MRI biomarkers in the MEMENTO cohort

Abstract: Introduction Subjective cognitive complaints may be a signature of preclinical stage Alzheimer's disease. However, the link between subjective cognitive and non‐cognitive complaints and brain alterations remains unclear. Methods The relationship between cognitive and non‐cognitive complaints and brain biomarkers, measured by structural magnetic resonance imaging, was investigated in 2056 participants of the MEMENTO cohort of outpatients, who were dementia‐free at baseline. We assessed whether the cognitive sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
(94 reference statements)
2
11
0
1
Order By: Relevance
“…Like some of the other studies, we did not find associations between TUG and hippocampal volume [51]. However, hippocampal degeneration may occur later in the degeneration process, reported mainly when cognitive symptoms are more pronounced [54].…”
Section: Discussionsupporting
confidence: 65%
“…Like some of the other studies, we did not find associations between TUG and hippocampal volume [51]. However, hippocampal degeneration may occur later in the degeneration process, reported mainly when cognitive symptoms are more pronounced [54].…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, subjective cognitive complaints, which are self-reported and subjective in nature, did not seem to a good measure for assessing cognitive health in this population, based on the lack of association with IGF-1. In contrast, subjective cognitive complaints reported by cognitively healthy older adults, have shown significant associations between the complaint scores and multiple brain degeneration markers ( 57 59 ). This discrepancy could lie in the ability of the patient to accurately appraise their own cognitive abilities, since our population had a high percentage of individuals with characteristics of MCI (75%), who could have dismissed minor cognitive issues as forgetfulness.…”
Section: Discussionmentioning
confidence: 85%
“…It is important to note that the definition of SCD posits that cognitive complaints are not necessarily limited to the memory domain, but may also include other cognitive domains [5,74]. Previous cross-sectional studies have also reported that, while remaining clinically normal, a higher SCD level is related to lower performance on global cognition [8,9,75,76], and more specific cognitive functions, including verbal episodic memory and executive functions [10].…”
Section: Discussionmentioning
confidence: 99%